Quantitative MRI in murine radiation‐induced rectocolitis: comparison with histopathological inflammation score. (6th February 2018) - Zappa, Magaly; Doblas, Sabrina; Cazals‐Hatem, Dominique; Milliat, Fabien; Lavigne, Jérémy; Daniel, Fanny; Jallane, Abelhak; Garteiser, Philippe; Vilgrain, Valérie; Ogier‐Denis, Eric; Van Beers, Bernard E.
Abstract : Murine radiation‐induced rectocolitis is considered to be a relevant animal model of gastrointestinal inflammation. The purpose of our study was to compare quantitative MRI and histopathological features in this gastrointestinal inflammation model. Radiation rectocolitis was induced by localized single‐dose radiation (27 Gy) in Sprague‐Dawley rats. T 2 ‐weighted, T 1 ‐weighted and diffusion‐weighted MRI was performed at 7 T in 16 rats between 2 and 4 weeks after irradiation and in 10 control rats. Rats were sacrificed and the histopathological inflammation score of the colorectal samples was assessed. The irradiated rats showed significant increase in colorectal wall thickness (2.1 ± 0.3 mm versus 0.8 ± 0.3 mm in control rats, P < 0.0001), normalized T 2 signal intensity (4 ± 0.8 versus 2 ± 0.4 AU, P < 0.0001), normalized T 1 signal intensity (1.4 ± 0.1 versus 1.1 ± 0.2 AU, P = 0.0009) and apparent and pure diffusion coefficients (ADC and D ) (2.06 × 10 −3 ± 0.34 versus 1.51 × 10 −3 ± 0.23 mm 2 /s, P = 0.0004, and 1.97 × 10 −3 ± 0.43 mm 2 /s versus 1.48 × 10 −3 ± 0.29 mm 2 /s, P = 0.008, respectively). Colorectal wall thickness ( r = 0.84, P < 0.0001), normalized T 2 signal intensity ( r = 0.85, P < 0.0001) and ADC ( r = 0.80, P < 0.0001) were strongly correlated with the histopathological inflammation score, whereas normalized T 1 signal intensity and D were moderately correlated ( r = 0.64, P = 0.0006, and r = 0.65, P = 0.0003, respectively). High‐field MRI features of single‐dose radiation‐induced rectocolitis in rats differ significantly from those of control rats. Quantitative MRI characteristics, especially wall thickness, normalized T 2 signal intensity, ADC and D, are potential markers of the histopathological inflammation score. Abstract : Rectocolitis is induced in rats with a single dose of 27 Gy delivered using a medical accelerator. High‐field MRI features (wall thickness, normalized T 2 and T 1 signal intensities and ADC measures) of irradiated rats differ significantly from MRI features of control rats, and are correlated strongly with histopathological inflammation score.